A regiospecific rhamnosyltransferase from Epimedium pseudowushanense catalyzes the 3-O-rhamnosylation of prenylflavonols. Issue 3 (21st December 2017) - Feng, Keping; Chen, Ridao; Xie, Kebo; Chen, Dawei; Guo, Baolin; Liu, Xiao; Liu, Jimei; Zhang, Min; Dai, Jungui
Abstract : A novel rhamnosyltransferase and a UDP-rhamnose synthase were characterized and applied to the biosynthesis of bioactive prenylflavonol rhamnosides. Abstract : Epimedium is used in traditional Chinese medicine and contains flavonol glycosides that exhibit multiple biological activities. These bioactive flavonol glycosides usually have a rhamnose moiety at the 3-OH position of prenylflavonols, such as icariin (9 ), baohuoside I (1a ) and baohuoside II (2a ). However, to date, no rhamnosyltransferase has been reported to catalyze the 3- O -rhamnosylation of prenylflavonols. In this article, a flavonol rhamnosyltransferase, EpPF3RT, was identified from E. pseudowushanense B. L. Guo. The recombinant enzyme regiospecifically transfers a rhamnose moiety to 8-prenylkaempferol (1 ) and anhydroicaritin (2 ) at the 3-OH position to form baohuoside II (1a ) and baohuoside I (2a ) in vitro . In addition, a UDP-rhamnose synthase gene, EpRhS, from E. pseudowushanense was functionally characterized and used to produce the UDP-rhamnose sugar donor. Furthermore, an engineered Escherichia coli strain containing EpPF3RT and EpRhS was established to produce baohuoside II (1a ) from whole cells. These studies indicate the significant potential of an enzymatic approach for the rhamnosylation of bioactive flavonoids in Epimedium plants and will provide a promising alternative for producing bioactive rhamnosylated flavonoids combined with other genes/enzymes by synthetic biology.